The Effect of the Somatic, Auditory, Visual, Intellectual (SAVI) Approach to Improve Students' Critical Thinking Skills on the Material of Work and Energy - Ulpiah, Syifa; Rizal, Rahmat; Susanti, Ernita (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
This study is motivated by students' low critical thinking skills in the material of work and energy and the lack of innovation in using approaches in learning Physics. Based on the initial test, it is known that the average percentage of students' Critical Thinking Skills (CTS) in physics is 30%, with a very low category. The effort made by the researcher to overcome this problem was to apply the Somatic, Auditory, Visual, and Intellectual (SAVI) learning approach. The purpose of this study was to determine the effect of the SAVI learning approach on students' critical thinking skills and to determine the improvement of students' critical thinking skills after implementing the SAVI approach in class X MIPA SMA Negeri 2 Singaparna Academic Year 2022/2023. The research method used is a quasi-experiment with a non-equivalent control group design. The population of this study was the entire X MIPA class of SMA Negeri 2 Singaparna. The research sample was taken using a purposive sampling technique. Data analysis techniques used include normality test, homogeneity test, hypothesis test, and N-Gain test. Based on the results of hypothesis testing at the level of significance (α = 0.05), it found > (1.97> 1.67) so that is accepted. The experimental class N-Gain test results obtained data 0.54 in the medium category. It means that the SAVI approach affects students' CTS, and SAVI facilitates students to increase their CTS.